2019
DOI: 10.1038/s41419-019-1439-y
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circBACH2 plays a role in papillary thyroid carcinoma by sponging miR-139-5p and regulating LMO4 expression

Abstract: Circular RNAs (circRNAs) are a class of non-coding RNAs that are broadly expressed in various biological cells and function in regulating gene expression. They are structurally stable and tissue-specific. However, the function of human circRNAs and the role of circRNAs in papillary thyroid carcinoma (PTC) remain to be determined. Herein, the function of circRNA circBACH2 was investigated in human PTC cells. First, we detected the expression of circBACH2 in PTC tissues and PTC cell lines by RT-PCR. FISH was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…hsa-miR-139-5p was identi ed to be downregulated in the primary tumor and further in PTC metastasis [44]. hsa-miR-139-5p was also able to be sponged by circBACH2 and relieved the suppression of the target gene LMO4 in PTC [45]. RIMS2 was identi ed as a novel target of hsa-miR-139-5p in this study.…”
Section: Discussionmentioning
confidence: 49%
“…hsa-miR-139-5p was identi ed to be downregulated in the primary tumor and further in PTC metastasis [44]. hsa-miR-139-5p was also able to be sponged by circBACH2 and relieved the suppression of the target gene LMO4 in PTC [45]. RIMS2 was identi ed as a novel target of hsa-miR-139-5p in this study.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, because of their covalently closed-structure, circRNAs are more stable and more suitable as efficacious biomarkers than linear-RNAs, such as lncRNAs and miRNAs [20]. For instance, circ_UVRAG [21], circ_BACH2 [22] and circ_ANKS1B [23] have been identified to be diagnostic or prognostic biomarker for gastric cancer, papillary thyroid carcinoma and breast cancer, respectively. Previous report has been demonstrated that hsa_circ_0027345 (a circRNA derived from linear LRIG3) was overexpressed in HCC tissues [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, circBACH2/miR-139-5p/LMO4 regulatory axis could be a promising treatment strategy for PTC patients. 172 Likewise, low expression of circRAPGEF5 plays an important role in suppressing the aggressive biological behaviors of PTC by sponging miR-198, this subsequently downregulated the expression of fibroblast growth factor receptor 1 (FGFR1), a target gene of miR-198. 173 Moreover, overexpression of circ_0025033 promoted proliferation and invasion of PTC by directly sponging miR-1231 and miR-1304, therefore, circ_0025033/miR-1231/miR-1304 signaling pathway was considered to be a new regulatory mechanism in PTC initiation and progression.…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 99%